"Teaching competencies for physical education teachers in light of comprehensive quality standards" (Al-Farooq Journal of Sciences, 2026)
This study aimed to determine the level of teaching competencies possessed by male and female physical education teachers and to identify their strengths and weaknesses in a way that contributes to developing their professional performance and improving the educational process in light of professional performance standards. The study population consisted of physical education teachers working in schools affiliated with the Education Directorate in Al-Zawiya City during the academic year (2025). The researcher adopted the descriptive analytical approach due to its suitability for the nature of the study. The study sample was selected using a simple random sampling method, where the basic sample consisted of (30) male and female teachers, while a pilot sample consisting of (8) male and female teachers was selected to verify the validity and reliability of the instrument.The researcher prepared the study instrument in the form of a questionnaire consisting of four dimensions of teaching competencies: planning, implementation, assessment, and professional development, based on relevant literature and previous studies. To verify the validity of the instrument, it was presented to a group of experts and specialists to review its items and assess their suitability for the study objectives. It was also applied to the pilot sample to ensure the clarity and comprehensibility of the items, and the reliability coefficient was calculated using Cronbach’s Alpha.For statistical data analysis, the study employed means, standard deviations, and percentages. In addition, the T-test was used to examine differences according to gender, one-way analysis of variance (ANOVA) was used to identify differences according to academic qualification and teaching experience, and Pearson correlation coefficient was used to examine the relationship between teaching competencies and professional performance effectiveness.The results showed that the level of teaching competencies among male and female physical education teachers ranged from moderate to high, with relatively higher levels in planning and professional development competencies, while assessment competencies showed a relative weakness. The results also revealed no statistically significant differences in teaching competencies attributable to gender or academic qualification, whereas statistically significant differences were found based on teaching experience in favor of teachers with more than 10 years of experience. Furthermore, a strong positive correlation was identified between teachers' possession of teaching competencies and their professional performance effectiveness.In light of the findings, the study recommended developing specialized training programs to enhance assessment skills among physical education teachers, activating continuous professional development programs, encouraging experience exchange among teachers, and developing periodic evaluation tools to monitor performance levels and improve the quality of the educational process.
Keywords: competencies, teaching competencies, standards